Investigating the Relationship between Computer Accounting Information Systems and E-Commerce Requirements in Iranian Service Companies Considering US-Canada Joint Project - Badran Badrani; Safieh Siadat (International Business and Accounting Research Journal, 2021)
Regarding a joint project of the United States and Canada, this study examines the relationship between computer accounting information systems and e-commerce requirements in Iranian service companies. The present study is applied in terms of purpose and descriptive-analytical in terms of method. The study population included service sector companies listed on the Iranian Stock Exchange (n=55). The statistical sample included all employees of accounting departments, including 48 people. Questionnaires were distributed to 48 employees in the accounting department for the study sample and were fully retrieved. To collect data and information, first through the sources, references, books, articles, and scientific journals available in libraries, and in addition to previous studies related to the subject of study, the Internet was used to address all new cases on the subject of study. To collect the initial data, a questionnaire was used based on the measurement tool, which was prepared and designed based on the joint plan of the United States and Canada according to the questions. The study's questionnaire questions were based on a five-point Likert scale and a joint American-Canadian project (Al-Qishi, 2003) and (Mahern, 2009). The reliability of the questionnaire was evaluated and confirmed by Cronbach's test. SPSS software and a one-sample t-test were used to analyze the data. The results show a statistically significant agreement between computer accounting information systems and e-commerce requirements in Jordanian service companies under joint US-Canadian projects.